Solar-dried small fish: A women-led innovation in the coastal fishing villages of Odisha, India - Shenoy, Neetha (WorldFish, 2022)
Presentation for UN Ocean Decade Satellite Activity ‘A Productive Ocean: Resilient aquatic food systems for a productive ocean (1 June 2022). 10 polyhouse solar driers were installed and operationalized in partnership with Mission Shakti, the Fisheries & Animal Resources Development (FARD). The program was scaled up through MSME and FARD to establish market linkages (both open and school feeding programs).